Hepatitis B in children with leukemia: the role of primary immunization - Aslam, P. K.; Riyaz, A.; Kumar, V. T. Ajith; Geeta, M. G. (International Journal of Contemporary Pediatrics, 2019)
Background: Children with cancer have a greatly enhanced risk of contracting hepatitis B infection due to immunosuppression secondary to chemotherapy and radiotherapy, frequent blood transfusions, bone and peripheral vein punctures, tissue damage and mucositis. During the past 3 decades, multimodality therapy for childhood leukemia has resulted in markedly improved survival. Inspite of screening and immuno prophylaxis, hepatitis B infection rates in children with leukemia are high. In view of this, we decided to study the prevalence of hepatitis B among children with leukemia in our institution, and the possible risk factors. Methods: This was a cross sectional study carried out at a tertiary pediatric care center in North Kerala among 104 children between 1 and 12 years of age on treatment for leukemia. Results: Among the 104 children, only 17 (16.3%) had received primary immunization against hepatitis B. Of the 87 children who had not received primary immunization, 44.8% (n=39) developed hepatitis B, compared to 11.8% (n=2) in the vaccinated group (p=0.01). Conclusions: This study highlights the importance of primary immunization against hepatitis B in children with leukemia, and the need for universal coverage.